2017
DOI: 10.4194/1303-2712-v17_3_07
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The nutritional profiles of wild mixed zooplankton (WM Z) and laboratory cultured Artemia nauplii were compared in the present study. WMZ samples were collected from Sulur lake and Ukkadam lake, Coimbatore, Tamil Nadu, South India. The WMZ from both lakes and Artemia nauplii were utilized for the estimation of biochemical constituents (protein, carbohydrate, lipid, moisture and ash), profiles of amino acids, and fatty acids. Results showed that the total protein content was found to be significantly (P<0.05) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…For aquatic animals, zooplankton is a good source of protein, lipids, and carbohydrates [51]. In the present study, the results of whole-body composition indicated that feeding an increasing ZBM significantly increased crude protein and decreased lipid and ash content of grey mullet.…”
Section: Discussionsupporting
confidence: 50%
“…For aquatic animals, zooplankton is a good source of protein, lipids, and carbohydrates [51]. In the present study, the results of whole-body composition indicated that feeding an increasing ZBM significantly increased crude protein and decreased lipid and ash content of grey mullet.…”
Section: Discussionsupporting
confidence: 50%
“…The correlation between number of zooplankton species and temperature is presented here. Physiological, metabolic activities and distribution of aquatic organisms generally depends on water temperature (21)(22)(23) . The number of zooplankton increases significantly with the increasing temperature.…”
Section: Resultsmentioning
confidence: 99%